2009
DOI: 10.1016/j.virol.2008.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of determinants involved in the stimulation of HIV-1 expression by Sam68

Abstract: Control of HIV-1 RNA processing is central to the replication of the virus. Previously, we demonstrated that the cellular protein Sam68 enhances HIV-1 structural protein expression and RNA 3' end processing. In this report, we show that Sam68 interacts with unspliced HIV-1 RNA and that other members of the STAR/GSG protein family also promote viral RNA 3' end processing. We define a portion of the GSG domain (Sam 97-255) as sufficient for enhancement of Rev-dependent expression. In contrast to Sam68, Sam 97-25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This may in part explain why mutations in ESE3 were found to influence Rev activity. 59 Like nucleolin, and sometimes together with nucleolin, hnRNP K increases the stability of cellular mRNAs. 29 It may therefore stabilize HIV-1 mRNAs containing the SLS2-A7 sequence.…”
Section: Methodsmentioning
confidence: 99%
“…This may in part explain why mutations in ESE3 were found to influence Rev activity. 59 Like nucleolin, and sometimes together with nucleolin, hnRNP K increases the stability of cellular mRNAs. 29 It may therefore stabilize HIV-1 mRNAs containing the SLS2-A7 sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Sam68 enhances protein expression from the intron-containing HIV-1 RNA to a much greater extent than the RNA nuclear export itself in a Gag-Pol reporter system (Coyle et al 2003). On the other hand, Δ410, a NLSdeleted Sam68 mutant, inhibits HIV-1 RNA translation through sequestering the unspliced HIV-1 RNA at the perinulcear bundles from the translation machinery (Soros et al 2001) or altering the viral ribonucleoprotein (RNP) complex (Marsh et al 2008;McLaren and Cochrane 2009). Our recent studies have also shown that Sam68 enhances and Δ410 inhibits HIV-1 nef mRNA translation through stress granule formation ).…”
Section: Sam68 Function In Hiv-1 Rna Translationmentioning
confidence: 99%
“…In contrast, the MPMV CTE has been shown to require host proteins, Tap (Nxf1), p15 (Nxt1), Sam68 [15], [16], [17] and the RNA helicase Dbp5 [14]. Sam68 may be involved in other aspects of HIV-1 gene expression including the Rev-RRE-Crm1 pathway [18], [19], [20], [21]. An HIV-1 packaging system based on MPMV CTE would not only allow one to target Rev function using dominant negative proteins or RNA based approaches, but also host proteins unique to the Rev-RRE-Crm1 RNA transport pathway [22].…”
Section: Introductionmentioning
confidence: 99%